A ANALYSIS OF THE IMPACT OF MINDFULNESS ON QUALITY OF LIFE IN PATIENTS WITH MULTIPLE SCLEROSIS: SYSTEMATIC REVIEW (International Journal of Scientific Research and Management (IJSRM), 2021)
This study aimed to investigate the impact of the mindfulness-based interventions program on the quality of life of patients with Multiple Sclerosis. A systematic review was carried out based on the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyzes). For an updated perspective on the topic, the selected articles were published from March 2014 to March 2019. Thus, 10 articles were included in the review and were thoroughly compared. A detailed assessment was carried out to measure the impact of the mindfulness protocol both on the general quality of life and on its specific domains. It can be observed that there is some homogeneity of the results regarding the benefits of the practice of mindfulness in the patients’ general quality of life. Moreover, there was greater evidence of the effects of meditative practice on the psychological domain when compared to the physical domain. Hence, the present study considers the mindfulness program a viable tool to address quality of life in patients with Multiple Sclerosis. The lack of Brazilian studies in the area is highlighted. Also, further studies to evaluate the practice of mindfulness continuously, such as cohort studies, are necessary to elucidate the long-term effects of the protocol.